Mapping sage‐grouse fence‐collision risk: Spatially explicit models for targeting conservation implementation - Bryan S. Stevens; David E. Naugle; Brian Dennis; John W. Connelly; Tim Griffiths; Kerry P. Reese (Wildlife Society Bulletin)
Abstract Recent research suggested greater sage‐grouse (Centrocercus urophasianus; hereafter, sage‐grouse) fence collision may be widespread, and fence‐marking methods have been developed for reducing prairie‐grouse collision in sagebrush‐steppe habitats. However, research also suggested sage‐grouse collision was highly variable, and managers implementing mitigation desire targeting tools to prioritize mitigation efforts as a function of risk. We fit collision‐risk models using widely available covariates to a sage‐grouse fence‐collision data set from Idaho, USA, and developed spatially explicit versions of the top model for all known sage‐grouse breeding habitats (i.e., within 3 km of leks) in 10 of 11 western states where sage‐grouse are found. Our models prioritize breeding habitats for mitigation as a function of terrain ruggedness and distance to nearest lek, and suggest that a relatively small proportion of the total landscape (6–14%) in each state would result in >1 collision over a lekking season. Managers can use resulting models to prioritize fence‐marking by focusing efforts on high risk landscapes. Moreover, our models provide a spatially explicit tool to efficiently target conservation investments, and exemplify the way that researchers and managers can work together to turn scientific understanding into effective conservation solutions. © The Wildlife Society, 2013